(3Ljf EjQs - (3HQhfJj(B, (3TGQdhJs 1816-1855; Bronte, Charlotte 1816-1855 ((3HjQhJs (3OGQ GdHMGQs, 2002)
(3jJfGhd GdcJGH bUI GdCH GdPj LGA ef CjQdfOG djUHM QGYj HGdcfjSI GdEfLdjRjI hdOjg SJI CHfGAs
(3bUUs
(3GdcJGH HGddZJjf GdYQHjI h GdEfLdjRjIs
1 5
Keywords: Arabic stories; (3GdbUU GdYQHjIs